2016
DOI: 10.1038/nn.4202
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin-4 receptor–regulated energy homeostasis

Abstract: The melanocortin system provides a conceptual blueprint for the central control of energetic state. Defined by four principal molecular components—two antagonistically acting ligands and two cognate receptors—this phylogenetically conserved system serves as a prototype for hierarchical energy balance regulation. Over the last decade the application of conditional genetic techniques has facilitated the neuroanatomical dissection of the melanocortinergic network and identified the specific neural substrates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
240
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(256 citation statements)
references
References 142 publications
(246 reference statements)
9
240
2
5
Order By: Relevance
“…T he main focus of research into the central melanocortin system has been on melanocortin-4 receptor(s) (Mc4r) and their relation to energy homeostasis, with relatively few studies addressing the role of Mc4r in cardiovascular control (1,2). However, it is clear that this system plays an important role in the control of blood pressure (BP) (3,4).…”
mentioning
confidence: 99%
“…T he main focus of research into the central melanocortin system has been on melanocortin-4 receptor(s) (Mc4r) and their relation to energy homeostasis, with relatively few studies addressing the role of Mc4r in cardiovascular control (1,2). However, it is clear that this system plays an important role in the control of blood pressure (BP) (3,4).…”
mentioning
confidence: 99%
“…In contrast, the proopiomelanocortin (POMC) expressing neurons of ARC are responsible for promoting satiety and cessation of feeding, in combination with increasing energy expenditure and weight loss. The functional transmitters of POMC-neurons are the bioactive products α-, β-and γ-melanocyte stimulation hormones; these are part of the melanocortin-peptides, which arise from POMCprocessing (Krashes, Lowell and Garfield, 2016). Subpopulations of ARC POMC neurons have also been reported to either co-release the neurotransmitter GABA or Glutamate (Atasoy et al, 2014).…”
Section: The Arcuate Nucleus Melanocortin Circuitrymentioning
confidence: 99%
“…The ARC POMC and AgRP neurons target most of the same brain areas, with the strongest innervation occurring in hypothalamic structures (such as the paraventricular hypothalamic nucleus (PVH), lateral hypothalamus, medial preoptic nucleus, dorsomedial hypothalamus) and the paraventricular thalamic nucleus (Wang et al, 2015;Betley et al, 2013;Atasoy 2008). Multiple studies have revealed that the appetite reducing effect of melanocortin signaling primarily is mediated by ARC POMC-neurons projecting to the PVH (as reviewed by Krashes, Lowell and Garfield, 2016). Interestingly, the use of modern techniques such as chemogenetics and optogenetics for activation of ARC AgRP and POMC neurons have demonstrated different temporal dynamics of this circuitry.…”
Section: The Arcuate Nucleus Melanocortin Circuitrymentioning
confidence: 99%
See 2 more Smart Citations